Auxin-to-Gibberellin Ratio as a Signal for Light Intensity and Quality in Regulating Soybean Growth and Matter Partitioning - Yang, Feng; Fan, Yuanfang; Wu, Xiaoling; Cheng, Yajiao; Liu, Qinlin; Feng, Lingyang; Chen, Junxu; Wang, Zhonglin; Wang, Xiaochun; Yong, Taiwen; Liu, Weiguo; Liu, Jiang; et al. (Frontiers in Plant Science, 2018)
The intensity and quality (red to far-red (R/Fr) ratio) of light directly affect growth of plant under shading. Gibberellins (GAs) and auxin (indole-3-acetic acid (IAA)) play important roles in mediating the shading adaptive responses of plants. Thus, the intensity and quality of the uncoupling light from shading were assessed to identify the influence of each component on the morphology and matter distribution of the leaf, stem, and petiole. This assessment was based on the changes in endogenous Gibberellin 1 (GA1) and IAA levels. Soybean plants were grown in a growth chamber with four treatments (normal (N), N+Fr, low (L), and L+Fr light). Results revealed that the reductions in photosynthetically active radiation (PAR) and R/Fr ratio equally increased height and stem mass fractions of the soybean seedling. The light intensity significantly influenced the dry mass per unit area and mass fraction of soybean leaves, whereas the light quality regulated the petiole elongation and mass fraction. Low R/Fr ratio (high Fr light) increased the soybean biomass by improving the photosynthetic assimilation rate and quantum yield of photosystem II. In addition, the IAA and GA1 levels in the leaf, stem, and petiole did not reflect the growth response trends of each tissue toward light intensity and quality; however, trends of the IAA-to-GA1 content ratios were similar to those of the growth and matter allocation of each soybean tissue under different light environments. Therefore, the response of growth and matter allocation of soybean to light intensity and quality may be regulated by the IAA-to-GA1 content ratio in the tissues of the soybean plant.